Business engagement for the SDGs in COVID-19 time: an Italian perspective. Issue 7 (11th April 2023) - Scarpa, Francesco; Torelli, Riccardo; Fiandrino, Simona
Abstract : Purpose: This paper aims to understand how companies addressed and revisited their sustainable development goals (SDGs) engagement during COVID-19. Design/methodology/approach: The study conducts semi-structured interviews with the sustainability managers of 16 Italian listed companies acting for the accomplishment of the SDGs. Then, the interviews' transcripts and the companies' sustainability reports were thematically analysed to tease out relevant findings. Findings: The findings show that companies have intensified their SDGs efforts during COVID-19, implementing an approach closer to the "Sustainability for Braving Crisis". The findings unveil the transformational mechanisms which determined and facilitated this improvement at three levels of the business SDGs engagement: "WHY" (general awareness and motivations), "HOW" (governance mechanisms, organizational structure and stakeholder dialogue) and "WHAT" (SDGs identification and prioritization and actions for the SDGs). These findings uncover the mechanisms through which a global crisis may prompt and catalyse sustainable business practices, acting as i) an inspirational and empowering event, ii) an organisational lever and iii) a reference point. Practical implications: This research has important implications for practice and policy, as it offers managers and stakeholders guidance to understand how companies have reshaped their sustainability practices during the pandemic and drives future corporate responses in times of crisis. Social implications: This study shows that a crisis may be a powerful lever to intensify business sustainability practices towards a better contribution to the SDGs. Originality/value: This study focuses on how companies have revised their SDGs practices when faced with a global crisis such as COVID-19.